STRATEGI PEMBINAAN MODERASI BERAGAMA SEBAGAI BENTENG EKSTREMISME DI MADRASAH - Nurkilat Andiono; Achmad Mudatsir R; Ratna Dewi (Hikmah: Journal of Islamic Studies, 2023)
AbstractThis research aims to describe strategies of fostering religious moderation as a bulwark of extremism at the Islamic elementary school of Tarbiyatul Islamiyah Paiton Probolinggo. This research uses a qualitative approach and a case study type of research. This research was carried out at Islamic elementary school of Tarbiyatul Islamiyah Paiton Probolinggo, and was carried out from July to August 2023. Data collection techniques were carried out by means of observation, interviews and documentation studies. Meanwhile, the data analysis technique uses the Miles and Huberman model with three analysis steps, namely data reduction, data presentation and drawing conclusions. The results of this research indicate that the Strategy of Fostering Religious Moderation as a bulwark for extremism at Islamic elementary school of Tarbiyatul Islamiyah Paiton Probolinggo is: Integration of religious moderation values in the at Islamic elementary school curriculum, Integration of religious moderation values in learning, Exemplary role models for teachers, moderate-religious habituation in Islamic elementary school.AbstrakPenelitian ini bertujuan untuk mendeskripsikan strategi pembinaan moderasi beragama sebagai benteng ekstrimisme di madrasah ibtidaiyah Tarbiyatul Islamiyah Paiton Probolinggo. Penelitian ini menggunakan pendekatan kualitatif dan jenis penelitian studi kasus. Penelitian ini dilaksanakan di MI Tarbiyatul Islamiyah Paiton Probolinggo, dan dilaksanakan pada bulan Juli sampai dengan Bulan Agustus 2023. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara dan studi dokumentasi. Sedangkan teknik analisis data menggunakan model Miles and Huberman dengan tiga langkah analisis, yaitu reduksi data, penyajian data dan penerikan kesimpulan. Hasil penelitian ini menunjukkan bahwa strategi pembinaan moderasi beragama sebagai benteng ekstermmisme di Madrasah Ibtidaiyah (MI) Tarbiyah Islamiyah Paiton Probolinggo ialah mengintegrasikan nilai-nilai moderasi beragama dalam kurikulum madrasah, mengintegrasikan nilai-nilai moderasi beragama dalam pembelajaran, serta role model keteladanan tenaga pendidik dan habituasi religius-moderat di Madrasah.